2020
DOI: 10.1186/s13213-020-01554-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm activity of symbiotic Bacillus species associated with marine gastropods

Abstract: Purpose: Generally, symbiotic marine bacteria are renowned for the synthesis of compounds with bioactive properties, and this has been documented in many previous studies. Therefore, the present study was aimed to isolate novel bacterial symbionts of gastropods that have the ability to synthesize bioactive compounds. These bioactive compounds could be used effectively as antibiofilm agents in order to overcome the problems associated with biofilm. Methods: The bacteria associated with the surface of marine gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Moreover, bacterial extracts from Streptomyces chrestomyceticus showed antimicrobial activity against Candida biofilms in concentrations ranging from 4 to 250 µg mL −1 [ 35 ], and extracts from three different species of Bacillus were able to inhibit Alteromonas sp. biofilms [ 36 ]. In this work, the antibiofilm activity of thirteen extracts from soil bacteria and insect gut bacteria is reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bacterial extracts from Streptomyces chrestomyceticus showed antimicrobial activity against Candida biofilms in concentrations ranging from 4 to 250 µg mL −1 [ 35 ], and extracts from three different species of Bacillus were able to inhibit Alteromonas sp. biofilms [ 36 ]. In this work, the antibiofilm activity of thirteen extracts from soil bacteria and insect gut bacteria is reported.…”
Section: Discussionmentioning
confidence: 99%
“…The Bacillus species used in this study and their accession number was provided in Table 1. The extraction process was carried out as previously described with some modifications (Viju et al, 2017;Viju et al, 2020). Briefly, 5ml aliquot of an overnight culture at an optical density of 0.2 at 600 nm (OD 600 ) was inoculated in a 500 ml flask containing marine nutrient broth (MNB) at half its capacity.…”
Section: Extraction Of Secondary Metabolitesmentioning
confidence: 99%
“…Another example is Taxol, previously obtained from a terrestrial plant, the Pacific yew [16], which was found afterwards to be a product of an endophytic fungus of the plant. Another reason to pursue symbiotic marine microorganisms is their ability to produce a greater variety of novel secondary metabolites than their free-living counterparts [17].…”
Section: Introductionmentioning
confidence: 99%